P2_6 SubMariana - Murgatroyd, Conan; Kinsman, Charlie; Stinton, James; Mott, Dan (Physics Special Topics, 2021)
The aim of this paper is to determine the physics behind travelling to the bottom of the Marianas Trench in an enclosed hollow steel sphere. It was calculated that for an outer radius of 1m, the sphere requires a wall of thickness 15.7 cm to withstand the pressure and would weigh an estimated 13.1 metric tonnes.